О РОЛИ МИКРООРГАНИЗМОВ ИММОБИЛИЗОВАННЫХ НА РАЗЛИЧНЫХ НОСИТЕЛЯХ В ОЧИСТКЕ СТОЧНЫХ ВОД - Убайдуллаева, А.К.; Еримова, А.Ж.; Калжанов, П.У.; Мырзамбетов, П.Ш. (SCIENCE and SOCIETY, 2018)
In the article it is told about various microorganisms living in the drinking water environment. The results of the received research works also are presented in the article.